COVID-19 Vaccine Uptake and Factors Associated With Being Unvaccinated Among Lesbian, Gay, Bisexual, Transgender, Queer, and Other Sexual Identities (LGBTQ+) New Yorkers. (20th May 2022) - Low, Andrea; Wright, Connor; Platt, Joey; Chang, Christiana; Mantell, Joanne E; Romero, Emily; Hoos, David; Mannheimer, Sharon; Greenleaf, Abigail; Castor, Delivette; El-Sadr, Wafaa M
Abstract: Routine data on vaccine uptake are not disaggregated by lesbian, gay, bisexual, transgender, queer, and other sexual identities (LGBTQ+) populations, despite higher risk of infection and severe disease. We found comparable vaccination uptake patterns among 1032 LGBTQ+ New Yorkers and the general population. We identified critical socioeconomic factors that were associated with vaccine hesitancy in this economically vulnerable population.